Should a register be kept of conscientious objectors to euthanasia in Spain? - Salinas Mengual, Jorge (International Journal of Human Rights, 2023)
This article presents an analysis of conscientious objection in the context of the recently approved organic law on euthanasia in Spain. The article supports the legal argument in favour of conscientious objection to participation in euthanasia procedures as a fundamental right, attempting to achieve a reasonable balance and accommodation between the rights of patients and those of health professionals. As for the limitation of fundamental rights, the additional implementation of a registry of objectors in Spain would undermine the essence and content of the fundamental right to conscientious objection. The study examines the negative consequences of such limitations on privacy, non-discrimination and the right not to declare personal beliefs, and offers possible arguments aimed at promoting democratic pluralism and social peace.
Publicación con el texto completo en acceso restringido
Keywords: conscientious objection; euthanasia; fundamental rights; proportionality; register of objectors; tolerance; JCR; Scopus